Neurotoxoplasmosis and aids cerebrospinal, fluid analysis in 96 patients: estudo do líquido cefalorraqueano em 96 pacientes - L. R. Machado; J. A. Livramento; A. Spina -França (Arquivos de Neuro-Psiquiatria)
The behavior of CSF inflammatory pattern in patients with AIDS and/or toxoplasmosis of the CNS is studied in 176 patients, divided in three groups. In the first group, 96 patients with toxoplasmosis and AIDS are considered; in the second group, 50 patients with toxoplasmosis without AIDS; in the third group, 30 AIDS patients without toxoplasmosis nor any other opportunistic infection. It is possible to conclude that patients with toxoplasmosis associated to AIDS exhibit CSF inflammatory pattern similar to patients with neurotoxoplasmosis without AIDS, except in respect to gamma globulin rates for which a cumulative effect can be detected.